Evaluation of drainage system and flood management in Semarang city: A case study of kali Semarang and its impact on flood and tidal flood reduction - Irawan, Bagus; Syafrudin, Syafrudin; Budihardjo, Mochamad Arief (Edelweiss Applied Science and Technology, 2025)
Semarang City faces recurrent flooding and tidal inundation due to an inadequate drainage system, rapid urbanization, and the adverse impacts of climate change. This study aims to evaluate the effectiveness of the Kali Semarang revitalization project in mitigating flood and tidal inundation while identifying key challenges in its implementation. A mixed-method research approach is adopted, integrating hydrological analysis using a rainfall-runoff model, GIS-based spatial mapping, and stakeholder interviews. The findings reveal a significant reduction in flood inundation, from 1,281.67 hectares in 2023 to 1,228.96 hectares in 2024, along with a decrease in the number of inundation points from 522 to 466 locations. Additionally, embankment construction and river dredging improved water flow capacity, reducing inundation duration from 10 to 6 hours per event. However, challenges such as high sedimentation rates, inadequate inter-agency coordination, and limited infrastructure maintenance funding persist. Practical recommendations include enhancing drainage capacity, optimizing real-time hydrological monitoring, and increasing community engagement in urban drainage maintenance. These findings contribute to evidence-based urban flood management strategies for climate-resilient cities.